Factors Influencing Organizational Resilience in Secondary Schools: Applying Structural Equation Modelling Approach - Vasayangkura, Thunphimol; Sisan, Boonchan (My University, 2026)
This study aims to examine the causal links between the variables affecting organizational resilience in secondary schools. The study selected 500 participants through multi-stage random sampling, which included school directors, deputy directors and heads of the subject groups. To gather information, the study used a structured questionnaire with a 5-point rating system to evaluate the concepts of organizational resilience, stakeholder network, organizational learning, transformational leadership, and organizational culture. To assess validity, reliability, and the correlations between the variables, the data were examined using structural equation modeling. The results indicate that stakeholder network, organizational learning, transformational leadership, and organizational culture directly impact organizational resilience. Additionally, transformational leadership indirectly impact organizational resilience through organizational learning and organizational culture, whereas organizational learning indirectly influences organizational resilience through stakeholder network. Moreover, organizational culture indirectly impacts organizational resilience through organizational learning. The research's empirical results have significant ramifications that can be used to inform the development and enhancement of models intended to increase organizational resilience in educational settings.
Keywords: organizational culture; organizational learning; Organizational resilience; stakeholder network; transformational leadership